The Role of Cyber Public Relations In Health Campaign In Pandemic Times - Isma Savitri; Cindy Meidina Trihapsari; Melynda Elen Cahyati (Kanal: Jurnal Ilmu Komunikasi, 2022)
Public communication during a pandemic is the main pulse in efforts to contain and accelerate the recovery from the impact of the Covid-19 pandemic. This article was prepared with the aim of examining the role and strategy of cyber public relations in maintaining public communication through health campaign activities in the midst of social distancing recommendations. The method of writing this article uses a literature review. The results of the study indicate that the opportunity for the development of cyber public relations arises from the significant growth of internet users during the pandemic. The biggest challenge in sharing digital information is the emergence of hoax news that causes disinformation and social panic. The cyber public relations development strategy begins with planning a situation analysis based on data and sources, involving public participation, and monitoring every activity. The cyber public relations in the health campaign during the pandemic was driven directly by the Covid-19 Handling Task Force which also held a public relations function and was represented digitally through the website www.covid19.go.id. The role of cyber public relations includes 1) technical communication; 2) communication facilitator; 3) expert preciber communication; and 4) problem solving facilitator.